Muhammad Nabi yang Dijanjikan - Aditiyawarman, Indra (Fakultas Dakwah IAIN Purwokerto, 2009)
Moslem believed that Muhammad Rasulullah is God’s messenger that delivered as light for all human being.prophecy about his arriving also have written on earlier holy books before Islam (torah and bible) exactly as said on Sura al-Baqarah [2] : 146 and al-A’raaf [7]: 157. It’s said that he will come to fulfill all prophecies in Bible, will revive and renew allprophets teaching before him. However, in reality Jews and Kristen people unfairly conceal this fact from Moslem and theirown religious believer, for hundreds years till recent days